Advanced Practice Nursing: A Strategy for Achieving Universal Health Coverage and Universal Access to Health - Denise Bryant-Lukosius; Ruta Valaitis; Ruth Martin-Misener; Faith Donald; Laura Morán Peña; Linda Brousseau
ABSTRACT Objective: to examine advanced practice nursing (APN) roles internationally to inform role development in Latin America and the Caribbean to support universal health coverage and universal access to health. Method: we examined literature related to APN roles, their global deployment, and APN effectiveness in relation to universal health coverage and access to health. Results: given evidence of their effectiveness in many countries, APN roles are ideally suited as part of a primary health care workforce strategy in Latin America to enhance universal health coverage and access to health. Brazil, Chile, Colombia, and Mexico are well positioned to build this workforce. Role implementation barriers include lack of role clarity, legislation/regulation, education, funding, and physician resistance. Strong nursing leadership to align APN roles with policy priorities, and to work in partnership with primary care providers and policy makers is needed for successful role implementation. Conclusions: given the diversity of contexts across nations, it is important to systematically assess country and population health needs to introduce the most appropriate complement and mix of APN roles and inform implementation. Successful APN role introduction in Latin America and the Caribbean could provide a roadmap for similar roles in other low/middle income countries.